English language writing from the perspectives of ESL learners' cognitive process in goal attainment - Liza Abdullah
Writing has always been one of the most challenging skills that English as second language (ESL) learners are expected to acquire. Hyland (2013) affirms that most ESL learners view writing as the most difficult language skill to master. At the International Islamic University Malaysia (IIUM), a big number of international students who undergo the pre-sessional English language programme either fail to meet the minimum requirement of the university's English Placement Test (EPT) or pass it with a very minimum requirement due to writing. Hence, this study seeks to investigate the issue of English language writing from the perspectives of pre-sessional international students' cognitive processes guided by Bandura's (1997) Theory of Social Cognitive: Process of Goal Realisation. The central question of this dissertation is “What are the cognitive processes of ESL learners in achieving their goals to become good writers?” Using a qualitative research methodology, data were collected via semi-structured interviews with seven informants and one focus group discussion which was comprised of six informants. The findings revealed that with some motivation, main goal, and little knowledge they had in writing, the informants were more inclined to highly depend on their teachers to achieve their goals in writing. This was found to be alarming, considering they were mature students of a higher learning institution. From the major findings, a framework termed the Model of ESL Learners' Cognitive Process towards Goal Attainment was proposed to guide international students and language teachers in achieving their goals in writing. Apart from being an added advantage to the university in terms of policy-making related to the students they are nurturing, the findings of this study may contribute vastly to the academic field from the aspects of curriculum design, teaching pedagogy, and teacher training at large.